'THE AFTERMATH EXPERIENCED BEFORE': AESCHYLEAN UNTIMELINESS AND IRIS MURDOCH'S DEFENCE OF ART. (December 2019) - Umachandran, Mathura
Abstract : This year marks the centenary of the birth of Iris Murdoch (1919–99). She has been celebrated as one of Britain's most important postwar writers with twenty-six prose fiction novels to her name. Murdoch was also an ancient philosopher who was primarily interested in issues of moral philosophy. Pinning down her place in the Anglo-American analytic tradition of philosophy, however, is not a straightforward task. On the one hand she cut a conventional figure, holding a tutorial fellowship at St Anne's College, Oxford, from 1948 to 1963. On the other hand, her philosophical writing increasingly departed from the coordinates of analytical philosophy. As Martha Nussbaum notes in her deeply ambivalent review of Murdoch's The Fire and the Sun: Why Plato Banished the Artists, Murdoch is 'a novelist whose best work is deeply philosophical, a philosopher who has stressed…the special role that beauty can play in motivating us to know the good, …a Platonist believer in human perfectability, and an artist.' Nussbaum points us towards understanding two key elements in Murdoch's thought: her commitment to Plato and the manner in which Murdoch's activity as philosopher and novelist should be considered as interdependent.